Pengaruh Beban Kerja, Stres Kerja, dan Motivasi Kerja Terhadap Kinerja Pegawai Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu Kabupaten Nganjuk - Ika Aditiyasningrum; Bambang Suwarsono; Nurali Agus Najibul Z (FEB Universitas Maritim Semarang, 2023)
Human resource management is one of the most important aspect in the course of a agency to achieve its vision, mission, strategy and the creation of agency goals. The aim of this research is to explain the influence of workload, work stress and work motivation on employee performance. This research uses a saturated sample. The sample in this study was 31 employees of the Nganjuk Regency Investment and One Stop Integrated Services Service. In this research, the results obtained were that workload, work stress and work motivation partially had a significant effect on the performance of employees of the Nganjuk Regency Investment and One-Stop Integrated Services Service. Meanwhile, simultaneously these three variables have a significant effect on the performance of employees of the Nganjuk Regency Investment and One Stop Integrated Services Service.